Analysis of The Influence of Import Volumes, Dynamics of Import Varieties, and Pricing Policies on Country's Foreign Exchange Growth - Reza Aulia, Muhammad; Kamar, Karnawi; Diah Astuti, Enny; Henri Kusnadi, Iwan; Parida, Parida (International Journal of Engineering, Science and Information Technology, 2024)
The objective of this research is to examine the factors that led to the cessation of imports of certain varieties after the crisis. This analysis proposes four alternative working hypotheses. Data from 100 products was taken. Several influencing factors reveal the impact of the economic crisis on imported varieties. More expensive varieties tend to experience an increased probability of stopping importation. This may be due to a decrease in purchasing power during the crisis, which makes expensive products less desirable. Geographic distance also plays an important role. More distant countries produce varieties with a higher probability of stopping imports, this could be due to higher transportation costs for varieties from distant countries. Varieties with a larger market share originating from countries with higher incomes tend to be more stable in the market during the crisis. Likewise, additional per capita income limits the probability of stopping imports to only 3.7%. This suggests that varieties from countries with high incomes or those with large market shares may have competitive advantages that make them more resilient to the impact of economic crises. Reducing imported varieties can hurt consumer welfare because it can reduce product choices and increase prices. Short-term estimates indicate a 9.5% decline in consumer welfare from imported goods.